Bioinformatic identification of exosomal phosphospecific biomarkers candidates for Alzheimer’s disease - Silva, Filipa Maria Avidos (2022)
Exosomes are a subtype of extracellular vesicles, important in cellular communication and involved in several physiological and pathological processes. In its content there are several molecules, including proteins with potential as biomarkers for diagnostic or therapeutic targets. In this context, studies that support the clinical value of these nanovesicles are being carried out for a variety of diseases, including for Alzheimer's disease (AD). AD is the most prevalent form of dementia worldwide with a great impact on the patients’ life and their families. The phosphorylation process is crucial in the disease’s progression and in the appearance of senile plaques (SPs) and neurofibrillary tangles (NFTs). The main goal of this work was to identify putative biomarkers’ candidates in the phosphoproteome of blood-derived exosomes. For this, it was performed a bioinformatic analysis of the exosomal phosphoproteome, obtained by microarrays’ analysis. 447 proteins were obtained, 48 of which had some described relation with AD. A Gene Ontology analysis of this phosphoproteome revealed several molecular events related to phosphorylation and focused on the identification of the kinases and phosphatases relevant to AD. The MAPK1 and CDK1 proteins were tested as putative biomarkers. Using Western Blot and ELISA, it was possible to detect a tendency to decrease the amount of MAPK1 in blood-derived exosomes of AD patients compared to controls. Future studies aim to test these candidates in a wider range of samples and validate their potential as diagnostic biomarkers for AD.